Expression, Localization, and Protein Interactions of the Partitioning Proteins in the Gonococcal Type IV Secretion System - Callaghan, Melanie M.; Koch, Birgit; Hackett, Kathleen T.; Klimowicz, Amy K.; Schaub, Ryan E.; Krasnogor, Natalio; Dillard, Joseph P. (Frontiers in Microbiology, 2021)
Partitioning proteins are well studied as molecular organizers of chromosome and plasmid segregation during division, however little is known about the roles partitioning proteins can play within type IV secretion systems. The ssDNA-secreting gonococcal T4SS has two partitioning proteins, ParA and ParB. These proteins work in collaboration with the relaxase TraI as essential facilitators of type IV secretion. Bacterial two-hybrid experiments identified interactions between each partitioning protein and the relaxase. Subcellular fractionation demonstrated that ParA is found in the cellular membrane, whereas ParB is primarily in the membrane, but some of the protein is in the soluble fraction. Since TraI is known to be membrane-associated, these data suggest that the gonococcal relaxosome is a membrane-associated complex. In addition, we found that translation of ParA and ParB is controlled by an RNA switch. Different mutations within the stem loop sequence predicted to alter folding of this RNA structure greatly increased or decreased levels of the partitioning proteins.